Sevoflurane sedation in COVID-19 acute respiratory distress syndrome: an observational study with a propensity score matching model - Consales, Guglielmo; Cappellini, Iacopo; Freschi, Benedetta; Campiglia, Laura; Parise, Maddalena; Zamidei, Lucia (Frontiers in Medicine, 2023)
Introduction The management of severe COVID-19-induced acute respiratory distress syndrome (C-ARDS) often involves deep sedation. This study evaluated the efficacy of sevoflurane, a volatile anesthetic, as an alternative to traditional intravenous sedation in this patient population. Methods This single-center, retrospective cohort study enrolled 112 patients with C-ARDS requiring invasive mechanical ventilation. A propensity score matching model was utilized to pair 56 patients receiving sevoflurane sedation with 56 patients receiving intravenous sedation. The primary outcome was mortality, with secondary outcomes being changes in oxygenation (PaO2/FiO2 ratio), pulmonary compliance, and levels of D-Dimer, CRP, and creatinine. Results The use of sevoflurane was associated with a statistically significant reduction in mortality (OR 0.40, 95% CI 0.18–0.87, beta = −0.9, p = 0.02). In terms of secondary outcomes, an increase in the PaO2/FiO2 ratio and pulmonary static compliance was observed, although the results were not statistically significant. No significant differences were noted in the levels of D-Dimer, CRP, and creatinine between the two groups. Conclusion Our findings suggest an association between the use of sevoflurane and improved outcomes in C-ARDS patients requiring invasive mechanical ventilation. However, due to the single-center, retrospective design of the study, caution should be taken in interpreting these results, and further research is needed to corroborate these findings. The study offers promising insights into potential alternative sedation strategies in the management of severe C-ARDS.